Sympathetic innervation of inguinal white adipose tissue in the mouse. Issue 7 (28th September 2020) - Huesing, Clara; Qualls‐Creekmore, Emily; Lee, Nathan; François, Marie; Torres, Hayden; Zhang, Rui; Burk, David H.; Yu, Sangho; Morrison, Christopher D.; Berthoud, Hans‐Rudolf; Neuhuber, Winfried; Münzberg, Heike
Abstract: Adipose tissue plays an important role in metabolic homeostasis and its prominent role as endocrine organ is now well recognized. Adipose tissue is controlled via the sympathetic nervous system (SNS). New viral, molecular‐genetic tools will soon allow a more detailed study of adipose tissue innervation in metabolic function, yet, the precise anatomical extent of preganglionic and postganglionic inputs to the inguinal white adipose tissue (iWAT) is limited. Furthermore, several viral, molecular‐genetic tools will require the use of cre/loxP mouse models, while the available studies on sympathetic iWAT innervation were established in larger species. In this study, we generated a detailed map for the sympathetic innervation of iWAT in male and female mice. We adapted iDISCO tissue clearing to process large, whole‐body specimens for an unprecedented view of the natural abdominal SNS. Combined with pseudorabies virus retrograde tracing from the iWAT, we defined the preganglionic and postganglionic sympathetic input to iWAT. We used fluorescence‐guided anatomical dissections of sympathetic nerves in reporter mice to further clarify that postganglionic axons connect to iWAT via lateral cutaneous rami (dorsolumbar iWAT portion) and the lumbar plexus (inguinal iWAT portion). Importantly, these rami carry axons that branch to iWAT, as well as axons that travel further to innervate the skin and vasculature, and their functional impact will require consideration in denervation studies. Our study may serve as a comprehensive map for future experiments that employ virally driven neuromodulation techniques to predict anatomy‐based viral labeling. Abstract : Preganglionic and postganglionic sympathetic inguinal white adipose tissue (iWAT) inputs are anatomically distinct from interscapular brown adipose tissue. Dorsolumbar and inguinal iWAT portions are innervated by anatomically distinct sympathetic nerves. Sympathetic postganglionic iWAT innervation reaches its target organ via lateral cutaneous rami of intercostal nerves T11–L1 and anterior cutaneous femoral nerve (as part of the lumbar plexus, L1) White adipocytes are sparsely innervated (sparse varicosities), while brown adipocytes (beige islands) show dense innervation (dense varicosities) in iWAT.